Meningkatkan Hasil Belajar Bahasa Indonesia Melalui Penerapan Model Pembelajaran Make A Match - Nurmalawati, Nurmalawati (JURNAL GLOBAL EDUKASI, 2017)
Abstract: The purpose of this class action research is to improve the ability to comprehend the content of reading and reading quickly by paying attention to correct punctuation and intonation through the Make a Match learning model with the subject matter of reading drama script in Indonesian lesson. The subject of this research is the students of class IX SMP Negeri 1 Pulau Rakyat. The results showed that the results of the learning process after research efforts to improve the ability to understand the contents of reading and reading quickly by paying attention to punctuation and correct intonation through the method make a match with the subject matter of reading drama script on Indonesian Language lessons reached an average of 78.28 on cycle I. After motivated the research done through cycle II average value to 84.06. Learning outcomes in the first cycle reached a classical learning completeness of 76.72% after cycle II was done reflection and the completion of classical learning achievement reached 85.7%. Thus it can be concluded that the application of Make A Match learning model can improve the ability to comprehend the content of reading and reading quickly by paying attention to punctuation and correct intonation on the subject matter of reading drama script in Indonesian lesson on the students of class IX SMPN 1 Pulau Rakyat. Keyword: make a match, speed reading, punctuation, intonation Abstrak: Tujuan penelitia tindakan kelas ini adalah untuk meningkatkan kemampuan memahami isi bacaan dan membaca cepat dengan memperhatikan tanda baca serta intonasi yang benar melalui model pembelajaran Make A Match dengan materi pokok membaca naskah drama pada pelajaran Bahasa Indonesia. Subjek penelitian ini adalah siswa kelas IX SMPN 1 Pulau Rakyat. Hasil penelitian menunjukkan bahwa Hasil proses belajar setelah penelitian upaya meningkatkan kemampuan memahami isi bacaan dan membaca cepat dengan memperhatikan tanda baca serta intonasi yang benar melalui metode make a match dengan materi pokok membaca naskah drama pada pelajaran Bahasa Indonesia mencapai nilai rata-rata 78,28 pada siklus I. Setelah termotivasi dilakukan penelitian melalui siklus II nilai rata-rata menjadi 84,06. Hasil belajar pada siklus I mencapai ketuntasan belajar klasikal sebesar 76,72% setelah siklus II dilakukan refleksi dan rekomendasi ketuntasan belajar klasikal mencapai 85,7%. Dengan demikian dapat disimpulkan bahwa penerapan model pembelajaran Make A Match dapat meningkatkan kemampuan memahami isi bacaan dan membaca cepat dengan memperhatikan tanda baca serta intonasi yang benar pada materi pokok membaca naskah drama pada pelajaran Bahasa Indonesia pada siswa kelas IX SMPN 1 Pulau Rakyat. Kata kunci: make a match, membaca cepat, tanda baca, intonasi